Pathway choices by Chinese students on business Masters degrees - Jones, Martin K.; Zhang, Yin (Journal of education for business, 2021)
For the past two decades, Chinese students have formed a substantial component of many business-related postgraduate degrees in UK Universities. However, there has been little research into what motivates Chinese students to choose one type of business degree over another. In this paper, we use student record data to analyze the choices made by Chinese students between more mathematically demanding and more literary pathways within one master's degree in international business.